(untitled) (The International Journal for Scientific Research, 2024)
International human rights law and international humanitarian law are two specialized areas of public international law. They exist as two distinct branches of law. Each branch has a different legal basis and origin. However, they share humanitarian ideals, and thus some areas of overlap appear in practice. The two systems share the responsibility for protecting the rights of human beings: Humanitarian law in times of armed conflict, and human rights law in times of peace and times of war as well. Because of this, in practice, it happens that the standards of international human rights law and international humanitarian law are applied simultaneously. At the same time, there are differences between these two legal systems that arise from the different circumstances involved in a state of war and a state of peace. Consequently, several questions arise regarding this relationship: Are the two branches mutually exclusive? Under what circumstances is humanitarian law applied, and how does this differ from the application of human rights law? What are the areas of overlap? What are the practical consequences of the legal problems resulting from the parallel application of the two legal frameworks? This paper does not aim to answer all of these questions, but rather its goal is to contribute to the current debate by presenting the similarities between human rights law and humanitarian law, areas of overlap, and situations of common application. We will also focus on the differences in this relationship, especially the differences in the field of protection guaranteed by legal standards, responsibility for violating the standards, as well as the exceptions allowed in implementing the standards. In one part of the paper, the principle of private law is applied in cases where one of the two branches is more specific in a concrete situation.